Molecular Analysis of Penner B, D Group's Campylobacter jejuni Strains Isolated from Humans, Chickens and Cattle by PFGE - SHINAGAWA, Kunihiro; ONO, Kazuaki; KAWAMORI, Fumihiko; OMOE, Katsuhiko; SAITO, Shihoko (Japanese Journal of Food Microbiology, 2005)
A total of 170 Penner B, D group Campylobacter jejuni strains isolated from humans, chickens and cattle were found to represent 80 different types by PFGE (pulsed-field gel electrophoresis) according to an investigation conducted by three institutes in Akita, Saitama, and Shizuoka prefectures. Fifteen PFGE types were identical between isolates from humans and chickens and one PFGE type was identical between those from humans and cattle. There were some PFGE types which were widespread in time as well as in geography. Our study indicates that there are some Campylobacter strains which spread throughout large areas and become the cause for repeated human infections. The strains examined were grouped into four major clusters (I-IV) on the basis of UPGMA (unweighted pair group method with averages). In group IV, eight PFGE profiles were identical between isolates from humans and chickens. This suggests that isolates from chicken meat and chicken liver, especially those classified into this group, are closely related to those from human Campylobacter infections.